A Dissentient Reformist: Shahab Ahmad and His Oeuvre - Muhammad Iqbal Awan; Dr. Hafiz Khurshid Ahmad Qadri (jihat-ul-islam, 2023)
While discussing the modern discipline of Islamic Studies, the name of Shahab Ahmad (1966 – 2015 AD) – an ex-professor of Islamic studies in Harvard University, USA – revolves in the minds. The quality life-span and the contributions of this iconic dissentient scholar is going to be discussed here in this paper. Being a son of a broad minded medical professional couple, he was raised in the shadow of the western educational system, right from his early life. The isolated learning of a Muslim student in non Muslim institutions parted his thinking from general Muslims. Dissenting in basic Islamic beliefs became his ultimate fashion, as he, confusingly, took the rituals, cultures and customs of a specific area’s Muslims as a subject matter of Islam. Having a very short life, he authored a couple of unpublished books, which can be attached well with his cosmopolitan ideas. Undoubtedly, he was an acknowledged asset of global academia due to his relentlessness and devotion to his work but his dissentient, ambitious and reformist soul made him very anxious to erase even the whole Islamic history and to start it from ‘year zero’. Shahab has contributed literarily with devotion, as he penned a number of books and articles in the field of Islamic history.